Walt disnep pinocchio story book (Grolier Books Lahore, 2020)
Pinocchio, a wooden puppet, dreams of becoming a real boy and embarks on a series of adventures. Guided by his conscience, represented by the cricket Jiminy, he learns valuable lessons about honesty, courage, and responsibility. His journey emphasizes the importance of being true to oneself.